2020
DOI: 10.1017/s1092852919001792
|View full text |Cite
|
Sign up to set email alerts
|

Economics of decriminalizing mental illness: when doing the right thing costs less

Abstract: The United States’ criminal justice system has seen exponential growth in costs related to the incarceration of persons with mental illness. Jails, prisons, and state hospitals’ resources are insufficient to adequately treat the sheer number of individuals cycling through their system. Reversing the cycle of criminalization of mental illness is a complicated process, but mental health diversion programs across the nation are uniquely positioned to do just that. Not only are these programs providing humane trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Post‐arrest diversion is another point in the pathway where mental health interventions could be cost‐effective, but again clear evidence is awaited. A US estimate suggested that mental health diversion can lead to over $1 billion in savings per year (Delgado et al., 2020).…”
Section: Economic Evidence Of Mental Health Interventions Along the C...mentioning
confidence: 99%
See 2 more Smart Citations
“…Post‐arrest diversion is another point in the pathway where mental health interventions could be cost‐effective, but again clear evidence is awaited. A US estimate suggested that mental health diversion can lead to over $1 billion in savings per year (Delgado et al., 2020).…”
Section: Economic Evidence Of Mental Health Interventions Along the C...mentioning
confidence: 99%
“…Based on this, mental health interventions can be categorised by their timing in relation to criminal behaviour: Point of contact: Some criminal behaviours, such as violence, can be the direct result of psychopathology. Mental health interventions can be delivered at this point. Post‐arrest: Growing attention is being paid to the ethical problem of ‘criminalisation of mental illness’ and the high costs associated with incarceration of people with mental illness (Delgado et al., 2020). This implies a need to make comparisons between diverting for mental health interventions versus continuing a regular CJS pathway. Incarceration/punishment: Interventions at this point refer to those designed for offenders/prison inmates with mental health needs, including specific interventions in forensic psychiatry. Post‐incarceration: Interventions can be provided at/after release from prison for people with mental health problems, including follow‐up services to avert future crime and improve health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, a fraction of the cost for incarceration would provide financing for mental health service provision which would have a better chance of bringing about recovery. Prior research suggests that improving access to mental health services might be effective in reducing criminal involvement (Delgado, 2020; Jácome, 2021). However in many countries, community mental health services operate independently from the criminal justice system (Kidia et al , 2017; Tamburello et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…But it is cheaper than the alternatives. 13 As leaders in the field of mental health, how do we make provision of that care a priority? In other words, how do we prevent the policy pendulum from continuing to swing between extremes of neglect within institutions and neglect outside of institutions?…”
mentioning
confidence: 99%